Personal values and academic performance of high school students - Gogorza, Melania Moralina (2003)
The study sought to identify the common metacognitive strategies employed by college students when confronted with academic difficulties, and to determine the types of help they seek in the classroom as well as the reasons for doing so. Adopting a descriptive qualitative research method, 42 student-respondents were purposively sampled. It was found that the qualities of teacher, qualities of classmate, classroom structure, self-disposition, and the relevance and the degree of difficulty of the subject matter were seen to be the antecedents of help-seeking behaviors among the participating college students
Thesis (M.A. Education : Guidance)--University of the Philippines, Diliman.
Keywords: High school students -- Attitudes. -- Philippines -- Muntinlupa City; High school students -- Social conditions. -- Philippines -- Muntinlupa City; Values -- Philippines -- Muntinlupa City; Academic achievement -- Philippines -- Muntinlupa City